Prognostic values of serum alkaline phosphatase and globulin levels in patients undergoing intravenous thrombolysis - Zhu, Hong-Jing; Sun, Xin; Guo, Zhen-Ni; Qu, Yang; Sun, Ying-Ying; Jin, Hang; Wang, Mei-Qi; Xu, Bao-Feng; Yang, Yi (Frontiers in Molecular Neuroscience, 2022)
Background: In previous studies, alkaline phosphatase (ALP) level was a prognostic factor for patients with ischemic stroke, and globulin level was associated with hemorrhagic transformation (HT) after intravenous thrombolysis (IVT). However, the association between these serum biomarkers and prognosis in patients with acute ischemic stroke (AIS) who undergo IVT remains unclear. This study aimed to investigate the characteristics of serum ALP and globulin levels after IVT and to assess the relationship between these serum biomarkers and prognosis. Methods: This retrospective study used a prospectively collected database. We included patients with AIS who received recombinant tissue plasminogen activator (rt-PA) IVT. Demographic information, vascular risk factors, laboratory test results, and other stroke-related data were collected for analysis. Clinical outcomes included HT and 3-month poor outcome (modified Rankin Scale scores ≥2) after IVT. The association of ALP and globulin levels with HT and poor outcome was investigated using multivariate logistic regression analysis. An individualized prediction model based on ALP and globulin levels for functional outcomes was established. Results: We enrolled 750 patients in this study; 452 patients (60.3%) had poor outcome, and 117 patients (15.6%) had HT after IVT. After adjusting for all confounders, serum globulin level (OR=1.055; 95% confidence intervals (CI): 1.006–1.107; P=0.028) was independently associated with HT in patients with IVT. Serum ALP (OR=1.009; 95% CI: 1.002–1.016; P=0.010) and globulin levels (OR=1.062; 95% CI: 1.020–1.107; P=0.004) were associated with 3-month poor outcome in these patients. The constructed individualized prediction model for the 3-month poor outcome comprised the National Institutes of Health Stroke Scale (NIHSS) score, Trial of Org 10172 in Acute Stroke Treatment (TOAST), history of antihypertensive therapy, ALP and globulin levels. The area under the curve of the training and validation sets were 0.726 and 0.706, respectively, revealing that the model had good discriminating power. The P-values for the Hosmer-Lemeshow test in the training and validation sets were 0.978 and 0.148, respectively, indicating the model had good calibration. Conclusion: This study found that higher serum globulin levels were independently associated with HT. Additionally, higher serum ALP and globulin levels were independently associated with a poor outcome in patients after IVT.